2007
DOI: 10.1197/jamia.m2457
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Project-specific Consent for Access to Personal Information for Health Research: What Is the Opinion of the Canadian Public?

Abstract: Most of the public supported alternatives to study-specific consent, but few supported use without any notification or consent. Consent choices for research use of one's health information should be documented in the medical record. The challenge remains how best to elicit those choices and ensure that they are up-to-date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 22 publications
12
106
1
Order By: Relevance
“…13 The observation that among those with a preference, roughly twice as many veterans preferred the opt-in model has been echoed elsewhere. 14,15 Assuming that the percentages of respondents who said they would participate under the respective models actually applied to the MVP study, recruiting 1,000,000 subjects would require asking 1,450,000 veterans using an optout method or 1,250,000 veterans using an opt-in method. In practice, however, the opt-out rate of one large cohort study has been reported to be <5%, and, in a small, randomized-controlled trial of opt-in and opt-out enrollment models, participants in the opt-out group were more satisfied than those who were asked to opt in.…”
Section: Discussionmentioning
confidence: 99%
“…13 The observation that among those with a preference, roughly twice as many veterans preferred the opt-in model has been echoed elsewhere. 14,15 Assuming that the percentages of respondents who said they would participate under the respective models actually applied to the MVP study, recruiting 1,000,000 subjects would require asking 1,450,000 veterans using an optout method or 1,250,000 veterans using an opt-in method. In practice, however, the opt-out rate of one large cohort study has been reported to be <5%, and, in a small, randomized-controlled trial of opt-in and opt-out enrollment models, participants in the opt-out group were more satisfied than those who were asked to opt in.…”
Section: Discussionmentioning
confidence: 99%
“…A small part of the 2007 Canadian survey of public opinion concerned secondary uses of medical data [13]. 84% of surveyed Canadian consumers agreed that electronic health records could be used for health research if personal identifiers were first removed.…”
Section: Discussionmentioning
confidence: 99%
“…This survey investigated alternatives to project specific consent for access to personal medical information for health research [13]. Results indicated support was strong for secondary uses pertaining to research.…”
Section: Earlier Surveys Of Consumers View Of Secondary Uses Of Medicmentioning
confidence: 99%
“…Several studies of citizens' and patients' opinions on biobanking have been carried out in different countries, for example (in alphabetical order), Canada, 3 Italy, 4 Japan, 5 Saudi Arabia, 6 and Sweden, 7 to name only a few. In the United Kingdom, surveys have been performed by leading institutions such as the Human Genetics Commission, 8 the National Cancer Registry, 9 and the Wellcome Trust jointly with the Medical Research Council.…”
Section: Examples Of Surveys About Citizens' and Patients' Opinions Omentioning
confidence: 99%